Strategic leadership and its role in crisis management from the perspective of a sample of Alfaisal University employees (The International Journal for Scientific Research, 2025)
This study aimed to identify the role of strategic leadership in crisis management at Alfaisal University, and to determine whether strategic leadership and strategic planning of managers, according to the variables of gender, age, job level, educational qualifications, and years of experience, have an impact on crisis management. A questionnaire consisting of 30 items belonging to five areas was distributed to a sample of (500) managers and employees, with (478) responding, representing (95.6%) of the returned questionnaires. The results of the study showed an impact of strategic planning in the dimensions (vision, values, and strategic objectives) on crisis management at Alfaisal University, and that the sample members' attitudes were generally highly positive. However, their attitudes towards the field of strategic organization were moderately positive. The results also indicated the absence of statistically significant differences between the arithmetic means of the respondents in all areas of the study attributable to job level, while differences were found attributable to the variables of gender, age, and years of administrative experience in some areas of the study.
Keywords: Planning, Strategic Planning; Crisis Management; Alfaisal University